To solve the equation \( x - 94 = -38 \), you can follow these steps:
-
Add 94 to both sides of the equation:
\[ x - 94 + 94 = -38 + 94 \]
-
This simplifies to:
\[ x = 56 \]
So, the solution of the equation \( x - 94 = -38 \) is \( x = 56 \).
?(1 point)
1 answer
To solve the equation \( x - 94 = -38 \), you can follow these steps:
Add 94 to both sides of the equation:
\[ x - 94 + 94 = -38 + 94 \]
This simplifies to:
\[ x = 56 \]
So, the solution of the equation \( x - 94 = -38 \) is \( x = 56 \).